2020
DOI: 10.3126/jkmc.v8i4.32387
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic pyeloplasty for pelvi-ureteric junction obstruction: Our single center experience

Abstract: Background: Open pyeloplasty is considered as the gold standard for the treatment of pelvi-ureteric junction obstruction. Laparoscopic pyeloplasty has added advantages with equivalent success rate and low complication rate. Objectives: The aim is to study our experiences in laparoscopic retroperitoneal and transperitoneal pyeloplasty. Methodology: Sixty-five patients with pelvi-ureteric junction obstruction were included in the study. The study was conducted between October 2016 and May 2019 at Kat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Various studies showed a success rate of >90% in LP, [10][11] which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Various studies showed a success rate of >90% in LP, [10][11] which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…8-9-The LP service is mostly limited to the central hospitals of Nepal due to its high technical demands and resources. [9][10] This study was designed to find out the renal functional outcome after analyzing the pre and post-operative differential renal function (DRF)…”
Section: Introductionmentioning
confidence: 99%